“New Mediterranean Biodiversity Records” July 2019 - STERN, NIR; BADREDDINE, ALI; BITAR, GHAZI; CROCETTA, FABIO; DEIDUN, ALAN; DRAGIČEVIĆ, BRANCO; DULČIĆ, JAKOV; DURGHAM, HANI; GALIL, BELLA S.; GALIYA, MOHAMMAD Y.; IKHTIYAR, SAMAR; IZQUIREDO-MUÑOZ, ANDREAS; et al. (Mediterranean Marine Science, 2019)
This is the second collective paper issued in 2019, currently amalgamates new knowledge on the Mediterranean geographic distributions of 17 species from five phyla (six aliens, three cosmopolitans, two east Atlantic records and six natives). The acknowledged species were reported from ten countries, mentioned here from west to east: Spain: first report of the east Atlantic grouper Cephalopholis taeniops in the western Mediterranean and an inclusion of Pontarachna puntulum and Litarachna communis to the pontarachnid fauna of Spain; Morocco: first record of Solea senegalensis from the Moroccan Mediterranean coast; Algeria: a valid confirmation for the presence of Sardinella maderensis; Malta: a first record of the Red Sea stomatopod Erugosquilla massavensis; Italy: a rare observation of the crab Paragalene longicrura from Siciliy and a further integration of the alien brown shrimp Penaeus aztecus to the commercial catch in Sicily; Montenegro: a first record of the Lessepsian bigfin reef squid Sepioteuthis lessoniana from the Adriatic Sea; Turkey: northernmost documentation of the Mediterranean flatworm Prostheceraeus giesbrechtii in the Aegean Sea; Israel: a solid confirmation for the population establishment of both the alien rock shrimp Sicyonia lancifer and two species of angelfish, and a first and deepest record of the crystalline goby Odondebuenia balearica; Lebanon: first record of the jellyfish Pelagia noctiluca; Syria: first records of the crown jellyfish Nausithoe punctate and the smallscale codlet Bregmaceros nectabanus.